Pengaruh Pendekatan Pembelajaran Berdiferensiasi Berbantuan Media Lumio terhadap Keterampilan Berpikir Kritis dan Hasil Belajar Siswa pada Materi Ekosistem Kelas VII SMP Negeri 26 Samarinda - Rahmayani, Novi; Maasawet, Elsje Theodora; Rambitan, Vandalita Maria Magdalena; Nasution, Ruqoyyah; Akhmad, Akhmad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The purpose of this study is to determine the effect of the differentiated learning approach assisted by Lumio media on critical thinking skills and student learning outcomes in class VII ecosystem materials at SMP Negeri 26 Samarinda. This study uses a Quasi-Experimental method with a Non-Equivalent Control Group Design. The sampling technique was carried out by purposive sampling. The research instruments were in the form of a test of critical thinking skills and learning outcomes which were analyzed using the T-Test test with a significant level of 0.05, and N-Gain to analyze the results. The results showed that the N-Gain of critical thinking skills in the experimental group was 0.62 (medium category), and in the control group was 0.50 (medium category). On the other hand, the N-Gain for learning outcomes in the experimental group was 0.63 (moderate category), while in the control group it was 0.51 (moderate category). The results of the hypothesis test analysis, critical thinking skills, and learning outcomes each had a significant value of 0.00<0.05, so that there was a significant influence of the Lumio-assisted differentiated learning approach on critical thinking skills and student learning outcomes. Thus, this approach is effectively used to improve the quality of learning in the ecosystem material of junior high school grade VII SMP Negeri 26 Samarinda.